The beginnings of the Roman Empire in contemporary formats (II): Celluloid Augustus (Minerva, 2017)
This article is the second part of a larger study on the presence of Emperor Augustus in popular culture, with special attention to the recreations of this figure in comic books and cinema. The focus here are the cinematic recreations of the Emperor projected in films and television series, such as Cleopatra, I, Claudius, Rome, Empire, Augusto. Il primo imperatore and Los cántabros.
Keywords: Augustus; popular culture; classical reception; cinema